2005
DOI: 10.1124/jpet.104.079780
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Reduces Atherosclerosis by Inhibition of Superoxide and Tumor Necrosis Factor-α Formation in Low-Density Lipoprotein Receptor-Null Mice Fed High Cholesterol

Abstract: This study shows that 6-[4-(1-cyclohexyl-1H-tetrazol-5-yl) butoxy]-3,4-dihydro-2(1H)-quinolinone (cilostazol) suppresses the atherosclerotic lesion formation in the low-density lipoprotein receptor (Ldlr)-null mice. Ldlr-null mice fed a high cholesterol diet showed multiple plaque lesions in the proximal ascending aorta including aortic sinus, accompanied by increased macrophage accumulation with increased expression of vascular cell adhesion molecule-1 (VCAM-1) and monocyte chemoattractant protein-1 (MCP-1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 33 publications
(35 reference statements)
3
70
1
3
Order By: Relevance
“…A previous report revealed that this drug reduces atherosclerosis by inhibiting superoxide TNF-α and activating endothelial nitric oxide synthase. 18 A short-term study also showed that cilostazol could reduce 23.6% of the serum level of hs-CRP in type 2 DM patients, although no mention was made of PAOD. 19 This improvement probably occurs as a result of the activation of endothelial nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report revealed that this drug reduces atherosclerosis by inhibiting superoxide TNF-α and activating endothelial nitric oxide synthase. 18 A short-term study also showed that cilostazol could reduce 23.6% of the serum level of hs-CRP in type 2 DM patients, although no mention was made of PAOD. 19 This improvement probably occurs as a result of the activation of endothelial nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies (3,20,28,41,46) have reported that cilostazol has beneficial effects on the cardiovascular system through several cellular pathways. For instance, cilostazol possesses the ability to inhibit not only PDE3 activity but also adenosine uptake (20,29).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that atherogenesis is closely related to the inflammatory and endothelial responses after injury (1,2).…”
Section: Introductionmentioning
confidence: 99%